Synthesis, characterization and biological evaluation of some novel sulfonylthiosemicarbazides - ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (TAYLOR & FRANCIS LTD, 2019)
A series of thiosemicarbazides were synthesized and structurally characterized by spectroscopic techniques (NMR, FT-IR) besides elemental analysis. These compounds were evaluated for their cytotoxicity against human breast cancer cell line MCF7 and prostate cancer cell line PC3 and nonmalignant fibroblast L929 cell line by MTT assay. Among the compounds, N-[2-(4-chlorophenyl)ethyl]-2-[(4-methylphenyl)sulfonyl]hydrazinecarbothioamide (3d) and 2-[(4-methylphenyl)sulfonyl]-N-[4-(trifluoromethoxy)phenyl]hydrazinecarbothioamide (3f) were found to display significant cytotoxicity with IC50 of 13.87 mu M (against PC3 cell line) and 1.47 mu M (against MCF7 cell line), respectively. These compounds were non-cytotoxic to normal cell line with IC50>100 mu M. Western blotting studies demonstrated that compound 3f induced apoptosis and caused cell death in the MCF7 and PC3 cell lines via an increase in Bax protein expression and a slight decrease in Bcl-2 protein expression. The gene expression ratio Bax/Bcl-2 showed the induction of mitochondrial apoptosis in cancer cell lines. All of synthesized compounds have also been tested for antioxidant activity and all compounds achieved strong inhibition of the DPPH radical. These findings showed that compound 3f, displays potential to be further explored in the development of new anticancer agents.
Keywords: Sulfonyl derivatives; anticancer activity; apoptosis; DPPH; thiosemicarbazide; BAX/BCL-2 RATIO; FREE-RADICALS; THIOSEMICARBAZIDES; CANCER; APOPTOSIS; ANTIFUNGAL